Expatriate performance in terrorism-endangered countries: The role of family and organizational support. Issue 5 (October 2015) - Bader, Benjamin; Berg, Nicola; Holtbrügge, Dirk
Highlights: Business in terrorism-endangered countries is increasingly important. Assigning expatriates in these countries often is also a "family matter". Expatriates suffering from safety-related family tensions perform worse. POS is an appropriate measure to diminish negative effects. Abstract: Expatriates are not only sent to industrialized countries with stable environmental conditions, but also to countries that bear high political, social, and even terrorist risk. Despite its practical relevance, the role of expatriates' families on assignments in terrorism-endangered countries has not been addressed yet. Integrating expatriate literature and family systems theory we investigate the family-related performance antecedents of 121 expatriate managers assigned to a terrorism-endangered country. We find evidence that safety-related intra-family tension significantly impedes expatriates' work performance. Perceived organizational support can help to diminish this influence. We discuss our results and conclude with further implications for theory and practice.